Effects of secukinumab on serum adipocytokines: preliminary data - A. Fassio; D. Gatti; P. Gisondi; G. Girolomoni; O. Viapiana; A. Giollo; M. Zamboni; M. Rossini; L. Idolazzi (PAGEPress Publications, 2017)
Psoriatic arthritis (PsA) is a chronic inflammatory disease that affects joints, connective tissues and the axial skeleton. Metabolic syndrome is an independent risk factor for psoriasis (Pso) development and is associated with more severe forms of Pso. Adipocytokines are secreted by white adipose tissue and are thought to link obesity with the development of metabolic and cardiovascular diseases. Secukinumab is a new monoclonal antibody with a different mechanism of action. This antibody selectively binds to and neutralizes interleukin-17 (IL-17) and it has shown efficacy in the treatment of PsA. The aim of this study was to evaluate the possible interferences of secukinumab on different adipocytokines. We enrolled 28 patients with PsA, classified with the CASPAR criteria. Serum samples were stored at baseline and then at the first, the third and the sixth month of therapy. Resistin, chemerin, adiponectin and C-reactive protein (CRP) were dosed. When tested globally, none of the adipokine tested showed any statistically significant variation. However, when the male group was tested, both resistin and chemerin at M6 showed a significant decrease from baseline. CRP did not show any variation at any time point. Our study demonstrated that treatment with secukinumab has little influence on the levels of adipokines tested within the first six months of treatment even though it might exert different influence between males and females from a metabolic perspective. Further studies with greater numbers of patients are needed to determine whether these preliminary results have clinical relevance.